The impact of SARS‑CoV‑2 treatment on the cardiovascular system : an updated review - Mohammed Ahmed, Akkaif; Abubakar, Sha’aban; Arturo, Cesaro; Ammar Ali, Saleh Jaber; Andrea, Vergara; Ismaeel, Yunusa; Abubakar Ibrahim, Jatau; Mustapha, Mohammed; G. Saravana, Govindasamy; Majed Ahmed, Al-Mansoub; Muhamad Ali Sheikh, Abdul Kader; Baharudin, Ibrahim (Springer Nature, 2022)
The coronavirus disease-2019 (COVID-19) pandemic has become a major global health problem. COVID-19 is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and exhibits pulmonary and extrapulmonary efects, including cardiovascular involvement. There are several attempts to identify drugs that could treat COVID-19. Moreover, many patients infected with COVID-19 have underlying diseases, particularly cardiovascular diseases. These patients are more likely to develop severe illnesses and would require optimized treatment strategies. The current study gathered information from various databases, including relevant studies, reviews, trials, or meta-analyses until April 2022 to identify the impact of SARS-CoV-2 treatment on the cardiovascular system. Studies have shown that the prognosis of patients with underlying cardiovascular disease is worsened by COVID-19, with some COVID-19 medications interfering with the cardiovascular system. The COVID-19 treatment strategy should consider many factors and parameters to avoid medication-induced cardiac injury, mainly in elderly patients. Therefore, this article provides a synthesis of evidence on the impact of diferent COVID19 medications on the cardiovascular system and related disease conditions.